Oncogenic Potential of the Nuclear Receptor Coregulator Proline-, Glutamic Acid–, Leucine-Rich Protein 1/Modulator of the Nongenomic Actions of the Estrogen Receptor - Rajhans, Rajib (2007)
Proline-, glutamic acid–, leucine-rich protein 1 (PELP1), a novel nuclear receptor coactivator, and its expression is deregulated in hormone-dependent cancers, including those of the breast, endometrium, and ovary. PELP1 interacts with estrogen receptor and modulates its genomic and nongenomic functions. In this study, we examined whether PELP1 functions as an oncogene. The overexpression of PELP1 in fibroblasts and epithelial model cells resulted in cellular transformation. PELP1 also enhanced the transformation potential of c-Src kinase in focus formation assays, and PELP1 overexpression potentiated estradiol-mediated cell migratory potential and anchorage-independent growth. Using PELP1-small interfering RNA, we provided evidence that endogenous PELP1 plays an essential role in E2-mediated anchorage-independent growth, cell migration, and cytoskeletal changes. When compared with control vector transfectants, breast cancer cells stably overexpressing PELP1 showed a rapid tumor growth in xenograft studies. Immunohistochemical analysis of PELP1 expression using a tumor progression array of 252 breast carcinomas and normal breast tissue specimens revealed that PELP1 expression is deregulated to a greater degree in higher grade node-positive invasive tumors than in normal breast tissue or ductal carcinoma in situ. Our data suggest that PELP1 is a potential oncogene, that its expression is deregulated during cancer progression, and that PELP1 may play a role in oncogenesis.